'Straining After Impossibilities': Textual Presentation and the Scrope Davies Find. (1st September 2013) - Anderson, Mark
Abstract : As well as being one of the most extraordinary moments in Shelleyan scholarship over the last fifty years, the discovery of the Scrope Davies notebook, for decades now, has proved itself to be an intriguing challenge for editors, not least in terms of how texts with multiple authority should be presented. In light of a new edition of Shelley's works which departs from many previous editions in its presentation of key poems from the notebook, this essay seeks to consider the relative merits of editorial decisions on textual presentation and their wider implications for both textual and literary criticism.